Respuesta :
y = -2x + 9
y = 4x - 3
y is isolated in both equations, thus you may set the expressions (-2x + 9) and (4x - 3) equal to each other and solve for x.
-2x + 9 = 4x - 3
Subtract 9 from both sides.
-2x + 9 - 9 = 4x - 3 - 9
-2x = 4x - 12
Subtract 4x from both sides.
-2x - 4x = 4x - 12 - 4x
-6x = -12
Divide both sides by -6.
-6x/-6 = -12/-6
x = 2
Substitute 2 for x into one of the original equations to find y.
y = 4x - 3 (given)
y = 4(2) - 3 (substitute)
y = 8 - 3 (multiply)
y = 5 (subtract)
Plug x- and y-values into original equations to check work.
5 = -2(2) + 9
5 = - 4 + 9
5 = 5
5 = 4(2) - 3
5 = 8 - 3
5 = 5
Answer:
x = 2 and y = 5; (2, 5).
Set the two equations equal to each other, because both equal y
-2x + 9 = 4x - 3
Isolate the x.
-2x (-4x) + 9 (-9) = 4x (-4x) - 3 (-9)
-2x - 4x = - 3 - 9
-6x = -12
Isolate the x. Divide -6 from both sides
-6x/-6 = -12/-6
x = 2
Place 2 for x in one of the equations
y = 4(2) - 3
Solve
y = 8 - 3
y = 5
x = 2, y = 5 is your answer
hope this helps
~Audiomachine